Germinação e armazenamento de sementes de Mimosa verrucosa Benth. Nativa da caatinga - Silva, Paloma Pereira da (2011)
Mimosa verrucosa (Leguminosae), popularly known as Jurema smooth, it is a typical bush tree species in northeastern Brazil. The objective of this study was to evaluate the effect on germination under different temperatures and pre-treatments, soaking determine a curve, to evaluate the effect of water restriction and storage on the germination of M. verrucosa. The tests were conducted in experimental randomized design with four replications of 25 seeds. The seeds were arranged in germination chambers at a temperature of 20 to 40 º C in order to determine the optimum temperature. After determining the seeds were subjected to pretreatments which consisted of mechanical scarification with sandpaper wall (No. 180) and chemical scarification using sulfuric acid (98%) for 3, 5 and 10 minutes. For the imbibition curve was constructed by weighing samples of 25 seeds for each period of soaking. For the simulation of fluid restriction, solutions of (PEG 6000) at different osmotic potentials (0.0, -0.2, -0.4, -0.6, -0.8, -1.0, -1,2 MPa). And for storage were tested three storage conditions (paper bag, plastic bag in the environment and in a cold glass) and two storage periods (3 and 6 months), in addition to absolute control. The parameters evaluated were: percentage of final germination (G%), mean time (GMT), average speed (VMG), germination speed index (IVG).The best results were observed in seeds treated with sulfuric acid for 10 minutes at 30° C temperature, which raises the rate of germination, which is low, slow and uneven. The imbibition phase was adjusted to the model. The fluid restriction was found that the maximum values for germination percentage were observed between potential -0 MPa (water) to -0.4 MPa. . The seeds of M. verrucosa can be stored for a short period of six months under conditions of low temperature and permeable.